1999
DOI: 10.1074/jbc.274.27.19276
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Adaptation of Glutathione S-Transferase P1–1

Abstract: Human glutathione S-transferase P1-1 (GST P1-1) is a homodimeric enzyme expressed in several organs as well as in the upper layers of epidermis, playing a role against carcinogenic and toxic compounds. A sophisticated mechanism of temperature adaptation has been developed by this enzyme. In fact, above 35°C, glutathione (GSH) binding to GST P1-1 displays positive cooperativity, whereas negative cooperativity occurs below 25°C. This binding mechanism minimizes changes of GSH affinity for GST P1-1 because of tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 24 publications
1
33
0
Order By: Relevance
“…Fig. 7, displaying alternative subunit conformations in equilibrium, is supported by studies of Ricci and coworkers (24) suggesting that wild-type GSTP1-1 as a whole somewhat behaves as a thermodynamic system which obeys the Le Chatelier principle. In fact, whenever a physical factor like temperature or viscosity forces the G-site to assume a low affinity conformation for GSH binding, GSTP1-1 opposes this perturbation by developing positive cooperativity and vice versa.…”
Section: Effect Of Key Residue On Dimer Formation and Thermalsupporting
confidence: 52%
See 2 more Smart Citations
“…Fig. 7, displaying alternative subunit conformations in equilibrium, is supported by studies of Ricci and coworkers (24) suggesting that wild-type GSTP1-1 as a whole somewhat behaves as a thermodynamic system which obeys the Le Chatelier principle. In fact, whenever a physical factor like temperature or viscosity forces the G-site to assume a low affinity conformation for GSH binding, GSTP1-1 opposes this perturbation by developing positive cooperativity and vice versa.…”
Section: Effect Of Key Residue On Dimer Formation and Thermalsupporting
confidence: 52%
“…Mutants G42A, C48S, and K55A display positive cooperativity (21)(22)(23). On the other hand, mutants Y50F (24) and Y50A (the present study) display negative cooperativity of GSH binding. Caccuri et al (24) suggested that Gly 42 , Cys 48 , and Lys 55 point mutations induce cooperativity by distorting the conformation of helix ␣2.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…The Y49F mutant was designed and produced by site-directed mutagenesis, carried out in a two-step polymerase chain reaction (15). Details of this procedure have been reported elsewhere (13). Finally, the Y49F mutant was expressed in TOP 10 Escherichia coli cells and purified as previously reported (14).…”
Section: Methodsmentioning
confidence: 99%
“…1), could participate in intersubunit communication between active sites of the dimer (1,12). Although some studies have already been performed with the mutant Y49F in the presence of co-substrate (13), there has been no thermodynamic study carried out on this mutant in the absence of the co-substrate.…”
mentioning
confidence: 99%